Effectiveness of Virtual Environment Desensitization in the Treatment of Agoraphobia - North, Max M.; North, Sarah M.; Coble, Joseph R. (International Journal of Virtual Reality, 1995)
The primary purpose of this study was to investigate the effectiveness of the virtual environment technology in the area of psychotherapy. Consequently, this study investigated the effectiveness of a virtual environment desensitization (VED) in the treatment of agoraphobia (fear of being in places or situations from which escape might be difficult or embarrassing). It was done with a traditional experimental design using N=60 subjects. Thirty subjects were placed in the experimental group and thirty subjects were placed in the control group. Two instruments were used: an Attitude Towards Agoraphobia Questionnaire (ATAQ) and the Subjective Unit of Discomfort Scale (SUDS). Only subjects in the experimental group were exposed to the VED treatment. The virtual environment desensitization was shown to be effective in treatment of subjects with agoraphobia (experimental group). The control group, or no-treatment group, did not change significantly. All the attitudes towards agoraphobic situation decreased significantly for the virtual environment desensitization group (experimental group) but not for control group. The average SUDS in each session decreased steadily across sessions, indicating habituation. This research, including the pilot studies, has established a new paradigm for utilizing virtual environment technology in the effective, economical, and confidential treatment of psychological disorders.